Efficacy and Safety of bimekizumab in elderly patients: real-world multicenter retrospective study - IL PSO (Italian Landscape Psoriasis) - D. Orsini; M. Megna; C. Assorgi; A. Balato; R. Balestri; N. Bernardini; A. Bettacchi; T. Bianchelli; L. Bianchi; G. Buggiani; M. Burlando; AMG. Brunasso; et al. (Taylor & Francis Group, 2024)
Purpose of the article: The aim of this multicenter observational study is to report data from real world on the use of bimekizumab in patients aged ≥ 65 years with moderate-to-severe plaque psoriasis. Elderly patients are poorly represented in clinical trials on bimekizumab for plaque psoriasis, and real-world studies are important to guide clinical choices.Materials and methods: A retrospective multicenter study was conducted in 33 dermatological outpatient clinics in Italy. Patients aged ≥ 65 years, with moderate-to-severe plaque psoriasis and treated with bimekizumab were enrolled. No exclusion criteria were applied. Bimekizumab was administered following the Italian Guidelines for the management of plaque psoriasis and according to the summary of product characteristics, in adult patients who were candidates for systemic treatments. Overall, 98 subjects were included, and received bimekizumab up to week 36. Clinical and demographic data were collected before the initiation of treatment with bimekizumab. At baseline and each dermatological examination (4, 16, and 36 weeks), clinical outcomes were measured by the following parameters: (1) PASI score; (2) site-specific (scalp, palmoplantar, genital, nail) Psoriasis Global Assessment (PGA). At each visit, the occurrence of any adverse events (AEs) was recorded, including serious AEs and AEs leading to bimekizumab discontinuation.Results: The mean PASI score was 16.6 ± 9.4 at baseline and significantly decreased to 4.3 ± 5.2 after 4 weeks (p < 0.001), and 1.1 ± 1.7 after 16 week (p < 0.001). This level of improvement was maintained after 36 weeks (p < 0.001). PASI ≤2 was recorded in 36 (36.7%) at week 4, 68% and 69.4% at week 16 and 36, respectively. By week 16, 86/98 (87.8%) patients reached PASI75, 71/98 (72.4%) obtained PASI90, and 52/98 (53.1%) PASI100. Binary logistic regression tests showed a significant association of PASI100 by week 4 with lower PASI at baseline. PASI 100 at 16 or 36 weeks was not associated with baseline PASI, obesity, age, gender, previously naïve state, and presence of psoriatic arthritis. Patients naïve to biologics at baseline had similar response to bimekizumab as non-naïve subjects.Conclusions: Bimekizumab is a suitable option for elder patients as it is effective, tolerated and has a convenient schedule.